News, psycosphere and the violence of information: transnational news agencies and the alienation of the Brazilian territory - Pasti, André (Sociedade & Natureza, 2018)
In the current period, events can only exist effectively through mass media. In this context, the news play an important role on the uses of the territory and on its reorganization. This paper analyzes the circulation of news in Brazil from a geographical point of view, questioning the centralization of the command of news flows on the transnational news agencies. It discusses especially the role of the three main players: Thomson Reuters, Agence France-Presse (AFP) and Associated Press (AP). Therefore, dynamics of the psychosphereof the Brazilian territory are investigated based on the news flows, approaching the concepts of territorial alienation and geographical events throught the agenda-setting power of these global news agencies.